Using a Community-Based Participatory Research Model to Encourage Parental Involvement in Their Children's Schools. Issue 3 (23rd July 2021) - Keller, JoDee G; Miller, Claudia; LasDulce, Chance; Wohrle, Rachel G
Abstract: Parental engagement with their children's education has been shown to have positive effects for children's academic outcomes; thus, learning ways to increase parental engagement can be beneficial for students. Because of the importance of understanding schools in the context of the community and the essential role that community can play in supporting schools, community-based participatory research (CBPR) may be a particularly effective approach to data collection because it engages community partners as well as parents and school personnel, and it gains information that leads to meaningful interventions. This study explored the use of CBPR within an economically and ethnically diverse school community with the intent of developing strategies to foster increased parental participation in their children's education. Social workers and social work students facilitated focus groups with parents and community stakeholders to explore ways to increase parental engagement in their children's school and to identify barriers to engagement. The article identifies next steps based on the recommendations of participants and describes the outcomes of preliminary implementation of these steps.